Modeling of the processes of development of professional thinking of teachers of the future drawing science - Turayev Khumoyiddin Abdugaffarovich (International Journal on Orange Technologies, 2020)
International law is an authoritative legal system that is In this article, an overview of the modeling of the processes of the development of professional thinking of teachers of the future drawing science is given